Social Participation and Disaster Risk Reduction Behaviors in Tsunami Prone Areas. - Nopphol Witvorapong; Raya Muttarak; Wiraporn Pothisiri (PLoS ONE, 2015)
This paper examines the relationships between social participation and disaster risk reduction actions. A survey of 557 households in tsunami prone areas in Phang Nga, Thailand was conducted following the 2012 Indian Ocean earthquakes. We use a multivariate probit model to jointly estimate the likelihood of undertaking three responses to earthquake and tsunami hazards (namely, (1) following disaster-related news closely, (2) preparing emergency kits and/or having a family emergency plan, and (3) having an intention to migrate) and community participation. We find that those who experienced losses from the 2004 tsunami are more likely to participate in community activities and respond to earthquake hazards. Compared to men, women are more likely to prepare emergency kits and/or have an emergency plan and have a greater intention to migrate. Living in a community with a higher proportion of women with tertiary education increases the probability of engaging in community activities and carrying out disaster risk reduction measures. Individuals who participate in village-based activities are 5.2% more likely to undertake all three risk reduction actions compared to those not engaging in community activities. This implies that encouraging participation in community activities can have positive externalities in disaster mitigation.